2014
DOI: 10.1088/1674-1056/23/10/107808
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-induced absorption in stacked metamaterials based on phase retardation

Abstract: Wan Ming-Li(万明理) a) † , Yuan Shu-Qing(袁书卿) a) , Dai Ke-Jie(代克杰) b) , Song Yue-Li(宋月丽) a) , Zhou Feng-Qun(周丰群) a) , and He Jin-Na(何金娜) a) a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…[31] Furthermore, Taubert et al theoretically and experimentally demonstrated that the coupling of a broad dipolar to a narrow dark quadrupolar plasmon resonance is possible while simultaneously allowing for a retardation-induced phase shift, resulting in the remarkable EIA phenomenon. [32] Most importantly, switching between the EIT and EIA can be realized by operating a phase shift between two resonators, [33,34] which possess a promising potential for applications in THz detecting, perfect absorbers, and switching. Nevertheless, at present, most research works about the EIT and EIA are based on traditional linearly polarized (LP) waves, and there is very little research on circularly polarized (CP) waves.…”
Section: Introductionmentioning
confidence: 99%
“…[31] Furthermore, Taubert et al theoretically and experimentally demonstrated that the coupling of a broad dipolar to a narrow dark quadrupolar plasmon resonance is possible while simultaneously allowing for a retardation-induced phase shift, resulting in the remarkable EIA phenomenon. [32] Most importantly, switching between the EIT and EIA can be realized by operating a phase shift between two resonators, [33,34] which possess a promising potential for applications in THz detecting, perfect absorbers, and switching. Nevertheless, at present, most research works about the EIT and EIA are based on traditional linearly polarized (LP) waves, and there is very little research on circularly polarized (CP) waves.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, artificially prepared metamaterial devices have demonstrated unique electromagnetic properties that originate from the coupled interaction between electromagnetic waves and designed periodic arrays of sub-wavelength air holes. [1][2][3][4][5] Of these designed metamaterial structures, selfsymmetric metal/dielectric/metal composite multilayer nanostructures have been studied most widely, both numerically and experimentally. [6][7][8][9][10] This is because this configuration offers enormous modulation flexibility over the effective medium parameters (including the effective permeability, effective permittivity and effective impedance).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] This is because artificial metamaterials associated with many novel optical properties [8][9][10][11][12] can lead to strong couplings between electric and magnetic responses attributed to their peculiar geometric structures as well as their unit sizes much smaller than the wavelength of radiation. [13][14][15][16][17][18] Utilizing these strong electromagnetic couplings in chiral geometric structures, the strong CD and optical activity can occur. [19][20][21][22][23][24][25][26] Recently, Kuwata-Gonokami et al have demonstrated that the giant optical activity could exist in two-dimensional gratings consisting of chiral gold nanostructures with subwavelength features.…”
Section: Introductionmentioning
confidence: 99%